Motivasi Terselebung Gerakan Politik dan Fundamentalis terhadap Muslim - Indra Harahap; Muhammad Rahma Doni (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Fundamentalism, in the dictionary Theories and Schools in Philosophy and Theology is a view that emerged in 1909 and is used generally to designate a particular style of conservative Protestantism. Fundamentalism's aim is to preserve the foundations of faith and to combat attempts to reinterpret the Bible and theology in the light of modern knowledge. There are two approaches to understanding the symptoms of fundamentalism, namely objectivism and subjectivism. From an objectivist perspective, it is understood that fundamentalism arises because religious texts provide such legitimacy. From a subjectivist perspective, which places individuals as subjects who actively define their lives with the outside world, all fundamentalism is not only understood because religious texts teach it that way. As stated above, that the outside world is also an entity that also influences a person in internalizing his religious teachings. The attitude of the Batu Bara people towards political and fundamentalist movements is still very strong and rooted among the elders and native sons of the Batu Bara area who adhere to Malay cultural customs. Batu Bara, which is located in Pesisir Pantai, is one of the regencies in the province of North Sumatra where the majority of the people are ethnic Malays. Keywords: Fundamentalism, School, Politics